Leveraging the Interdependencies Between Barrier Islands and Backbarrier Saltmarshes to Enhance Resilience to Sea-Level Rise - Hein, Christopher J.; Fenster, Michael S.; Gedan, Keryn B.; Tabar, Jeff R.; Hein, Emily A.; DeMunda, Todd (Frontiers in Marine Science, 2021)
Barrier islands and their backbarrier saltmarshes have a reciprocal relationship: aeolian and storm processes transport sediment from the beaches and dunes to create and build marshes along the landward fringe of the island. In turn, these marshes exert a stabilizing influence on the barrier by widening the barrier system and forming a platform onto which the island migrates, consequently slowing landward barrier migration and inhibiting storm breaching. Here, we present a novel framework for applying these natural interdependencies to managing coastal systems and enhancing barrier-island resilience. Further, we detail application of these principles through a case study of the design of a marsh creation project that showcases the interdisciplinary engagement of scientists, engineers, stakeholders, and policymakers. Specifically, we describe (1) the ecologic, sedimentologic, stratigraphic, and morphologic data obtained from the southern 4 km of Cedar Island (Virginia, USA) and nearby backbarrier tidal channels, tidal flats, and flood-tidal deltas and (2) the use of those data to develop an engineering and design plan for the construction of a high (46 ha) and low (42 ha) fringing marsh platform located behind the island, proximal to a former ephemeral inlet. Additionally, we chronicle the process used to narrow five initial alternative designs to the optimal final plan. This process involved balancing best-available existing science and models, considering design and financial constraints, identifying stakeholder preferences, and maximizing restoration benefits of habitat provision and shoreline protection. Construction of this marsh would (1) provide additional habitat and ecosystem benefits, (2) slow the rapid migration (up to 15 m/yr at present) of the barrier island, and (3) hinder island breaching. Ultimately, this project—presently at the final design and permitting stage—may enhance the storm and sea-level rise resilience of the island, backbarrier marshes and lagoons, and the mainland town community; and provide an example of a novel science-based approach to coastal resilience that could be applied to other global barrier settings.